Role of microglia in the dissemination of Zika virus from mother to fetal brain. - Pei Xu; Chao Shan; Tiffany J Dunn; Xuping Xie; Hongjie Xia; Junling Gao; Javier Allende Labastida; Jing Zou; Paula P Villarreal; Caitlin R Schlagal; Yongjia Yu; Gracie Vargas; et al. (Public Library of Science (PLoS), 2020)
Global Zika virus (ZIKV) outbreaks and their link to microcephaly have raised major public health concerns. However, the mechanism of maternal-fetal transmission remains largely unknown. In this study, we determined the role of yolk sac (YS) microglial progenitors in a mouse model of ZIKV vertical transmission. We found that embryonic (E) days 6.5-E8.5 were a critical window for ZIKV infection that resulted in fetal demise and microcephaly, and YS microglial progenitors were susceptible to ZIKV infection. Ablation of YS microglial progenitors significantly reduced the viral load in both the YS and the embryonic brain. Taken together, these results support the hypothesis that YS microglial progenitors serve as "Trojan horses," contributing to ZIKV fetal brain dissemination and congenital brain defects.